Differential expression of ferroptosis-related proteins in urinary exosomes: potential indicators for monitoring acute gout attack - Wang, Jitu; Lin, Yubin; Liu, Na; Hu, Mei; Zhang, Man (Frontiers in Molecular Biosciences, 2024)
BackgroundGout is the most prevalent form of inflammatory arthritis, characterized by significant pain during acute episodes. Current diagnostic and monitoring techniques are invasive and fail to predict the onset of acute attacks. Recent studies have implicated ferroptosis-related proteins in the pathogenesis of inflammation and gout; however, their clinical relevance in gout patients remains largely unexplored. This study aimed to evaluate the expression of these proteins in urinary exosomes from gout patients and to investigate their potential as noninvasive biomarkers.MethodsUtilizing data-independent acquisition (DIA) mass spectrometry and advanced bioinformatics techniques, we assessed the expression of ferroptosis-related proteins in the urinary exosomes of three groups: acute gout patients (AD group), intermittent gout patients (ID group), and normal controls (NC group). We constructed receiver operating characteristic (ROC) curves to determine the clinical utility of these proteins in monitoring acute gout attacks.ResultsOur analysis of urinary exosome proteomics identified 13 ferroptosis-related proteins. Notably, in comparison to the ID group, the proteins ACSL4, VDAC2, GPX4, and GSS were significantly upregulated in the AD group. ROC curve analysis revealed that the presence of ACSL4, VDAC2, and GPX4 in urinary exosomes possesses substantial predictive value for acute gout attacks.ConclusionIn patients with gout, numerous protein alterations occur within urinary exosomes. Specifically, changes in ferroptosis-related proteins such as ACSL4, VDAC2, GPX4, and GSS may serve as promising biomarkers for the monitoring of acute gout attacks.